2020
DOI: 10.31557/apjcp.2020.21.7.2163
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-Affecting Single Nucleotide Polymorphisms (SNPs) in RPS6KA1 and MBIP Genes are Associated with Breast Cancer Risk

Abstract: Background: Genetic mutations and polymorphisms play an important role in the transformation of primary cells to malignant cells as it may lead to disturbance of vital pathways regulating cell cycle, DNA damage repair, and apoptosis. In this study, we genotyped single nucleotide polymorphisms (SNPs) which were predicted to affect certain pathways and to increase the risk of breast cancer. Methods: The study included 81 Saudi breast cancer patients and 100 matching healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is a component of the Ada2A containing complex (ATAC), which is involved in histone H3 and H4 modi cation. In earlier research, MBIP was identi ed as a susceptibility gene for thyroid cancer, breast cancer and non-small cell lung cancer (NSCLC) using genome-wide association studies (GWAS) (Genome-Wide Association Studies) [20][21][22][23][24]. However, it has only been reported in NSCLC that MBIP plays a potential role in metastasis, and in-depth investigation of the molecular mechanism has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…It is a component of the Ada2A containing complex (ATAC), which is involved in histone H3 and H4 modi cation. In earlier research, MBIP was identi ed as a susceptibility gene for thyroid cancer, breast cancer and non-small cell lung cancer (NSCLC) using genome-wide association studies (GWAS) (Genome-Wide Association Studies) [20][21][22][23][24]. However, it has only been reported in NSCLC that MBIP plays a potential role in metastasis, and in-depth investigation of the molecular mechanism has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that certain genes, such as oncogenes and tumor suppressor genes, are risk factors for many types of cancer (20)(21)(22)(23)(24). When activated, oncogenes stimulate tumor growth whereas tumor suppressor genes prevent tumor growth and development.…”
Section: Introductionmentioning
confidence: 99%